Monosaccharide profile and antioxidant activities of sulphated polysaccharide extracted from Indonesian brown seaweed (Sargassum sp.) - Lim, Seng Joe; Sharifah Habibah Syed Khalafu,; Böhmdorfer, Stefan; Rosenau, Thomas; Mohamad Yusof Maskat,; Noor Soffalina Sofian Seng,; Noorul Syuhada Mohd Razali,; Wan Aida Wan Mustapha, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This research was conducted to determine the monosaccharide profile and antioxidant activities of the sulphated polysaccharide fucoidan, extracted from Sargassum sp. harvested in Batam, Indonesia. Crude fucoidan (Fsar) was extracted using low pH (pH 2) acid method, obtaining a yield of 5.5% (w/w), and the chemical properties of Fsar were subsequently compared to commercial fucoidan (Fcomm), obtained from Japan. Sulphate contents were determined using spectrophotometric analysis, where Fsar (5.21±0.35%) and Fcomm (8.80±0.19%) differed significantly (p<0.05). Monosaccharide profiling was performed using methanolysis and gas chromatography-flame ionisation detector (GC-FID). Fsar contained fucose (138.34 µg/g), 4-O-methyl-glucuronic acid (105.39 µg/g), galactose (70.49 µg/g) and glucuronic acid (30.60 µg/g) while Fcomm contained fucose (520 µg/g) and glucuronic acid (62.93 µg/g) as its main composition. Antioxidant activities were analysed through 2,2-diphenyl-1-picrylhydrazyl (DPPH), superoxide anion (SOA) and hydroxyl radical (·OH) scavenging activities. DPPH scavenging activity of Fsar (40.67±4.0%) was significantly higher (p<0.05) than Fcomm (10.11±1.0%), while SOA and ·OH scavenging activities showed no significant difference (p>0.05) between Fsar and Fcomm. Fsar showed significant differences (p<0.05) in chemical properties and DPPH scavenging activities compared to that of Fcomm. Fucoidan from Southeast Asia waters has the potential for application as functional ingredients.